The eight-wheel locomotive DC3 with the second type of rating unloading and additional loading of wheels and deflections spring suspension during traction efforts transfer from bogies to body with using reclining tractions - Bratash, V. A.; Efimova, T. I.; Povolotskaya, YU. V. (Science and Transport Progress, 2011)
In the article the calculation formulas for determination of unloadings (finishings loadings) of wheels and bendings of a spring suspension of 8-wheel electric locomotive DS 3 with the hauling transmission of the second kind at the transmission of tractive forces from the bogies to the body through sloping tractions are presented. Numerical calculations are executed on the example of mainline freight-and-passenger electric locomotive DS 3.